Devastating impacts of COVID-19: An experience of abandoned child at a tertiary care hospital - Deepali Thakur; Navneet Dhaliwal; Sruti Sharma; Anil Kumar Gupta (Wolters Kluwer Medknow Publications, 2021)
There were many challenges faced by both health-care workers and the common population during the COVID-19 pandemic. One such case was witnessed where a migrant worker abandoned his child in a tertiary care hospital, while he was undergoing treatment for acute liver disease and was reported COVID-19 positive. The child was treated for COVID-19 in the dedicated isolation facility of the hospital as per the guidelines. Later, when the child was declared COVID-19 negative and was ready to discharge, treating doctors found it difficult to hand over the child. The timely intervention and extraordinary efforts by the department of hospital administration and child welfare committee reunited the child with his family.